Combined flow cytometry natural killer immunophenotyping and KIR/HLA-C genotyping reveal remarkable differences in acute myeloid leukemia patients, but suggest an overall impairment of the natural killer response - Cianga, Vlad Andrei; Rusu, Cristina; Pavel-Tanasa, Mariana; Dascalescu, Angela; Danaila, Catalin; Harnau, Sebastian; Aanei, Carmen-Mariana; Cianga, Petru (Frontiers in Medicine, 2023)
Natural Killer (NK) cells are key anti-tumor effectors of the innate immunity. Phenotypic differences allow us to discriminate in between three functional stages of maturation, named immature, mature and hypermature that are distinctive in terms of receptor expression, cytokine secretion, cytotoxic properties and organ trafficking. NKs display an impressive repertoire of highly polymorphic germline encoded receptors that can be either activating, triggering the effector’s function, or inhibitory, limiting the immune response. In our study, we have investigated peripheral blood NK cells of acute myeloid leukemia (AML) patients. The Killer Immunoglobulin-like receptors (KIRs) and the HLA-C genotypes were assessed, as HLA-C molecules are cognate antigens for inhibitory KIRs. The AA mainly inhibitory KIR haplotype was found in a higher proportion in AML, while a striking low frequency of the 2DS3 characterized the mainly activating Bx haplotype. Flow cytometry immunophenotyping evidenced a lower overall count of NK cells in AML versus healthy controls, with lower percentages of the immature and mature subpopulations, but with a markedly increase of the hypermature NKs. The analysis of the KIR2DL1, KIR2DL2, KIR2DL3, KIR3DL1 and NKG2A inhibitory receptors surface expression revealed a remarkable heterogeneity. However, an overall trend for a higher expression in AML patients could be noticed in all maturation subpopulations. Some of the AML patients with complex karyotypes or displaying a FLT3 gene mutation proved to be extreme outliers in terms of NK cells percentages or inhibitory receptors expression. We conclude that while the genetic background investigation in AML offers important pieces of information regarding susceptibility to disease or prognosis, it is flow cytometry that is able to offer details of finesse in terms of NK numbers and phenotypes, necessary for an adequate individual evaluation of these patients.